Combined experimental and theoretical studies of pressure effects in La2Sb - Knöner, Stephan; Gati, Elena; Wolf, Bernd; de Souza, Mariano [UNESP]; Haghighirad, Amir; Kuhnt, Markus; Assmus, Wolf; Jeschke, Harald O.; Tomić, Milan; Valentí, Roser; Lang, Michael (Wiley, 2017)
The 5 K superconductor La2Sb shares some structural similarities with the iron-pnictides and -chalgogenides, especially the so-called 122-compounds, despite lacking a 3d-metal component. In order to look for similarities and dissimilarities of this layered metal pnictide with the higher- Tc Fe-based superconductors, we have performed a combined experimental and theoretical investigation of the effects of hydrostatic pressure. Magnetic measurements reveal a linear increase of Tc with pressure at a rate dc/dP = (0.71 ± 0.01)KGPa−1. Band structure calculations show that (i) the states at the Fermi level have predominantly La 5d character and (ii) that the density of states increases linearly with increasing pressure. By using these theoretical results and a BCS formalism, a quantitative description of the experimentally revealed pressure dependence of Tc is possible within a reasonable range of parameters. Our results indicate that La2Sb, despite its structural similarities to the 122 Fe-based superconductors, exhibits a BCS-type of superconductivity.
Keywords: La2Sb; iron pnictides; pressure effects; superconductivity